2006
DOI: 10.1002/cncr.21789
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, epigenetic, and clinicopathologic features of gastric carcinomas with the CpG island methylator phenotype and an association with Epstein–Barr virus

Abstract: BACKGROUNDThe CpG island methylator phenotype (CIMP), which is characterized by simultaneous methylation of the CpG islands of multiple genes, has been recognized as one of the important mechanisms in gastrointestinal carcinogenesis.METHODSMethylation of the 5 methylated‐in‐tumors (MINT) loci and 12 tumor‐related genes in 78 primary gastric carcinomas was examined using combined bisulfite‐restriction analysis. Epstein–Barr virus (EBV)‐associated gastric tumors were detected using real‐time polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
150
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 39 publications
5
150
3
2
Order By: Relevance
“…23,24,26,27 They also show a lack of TP53 mutations. 6,23,24,28,29 This trend was also recorded in the Asian Cancer Research Group data set. 7 It has been suggested that the profound global DNA effects are responsible for the distinctive clinicopathologic features of EBV gastric cancers 20 including male predominance 9,30 and proximal location.…”
Section: Discussionsupporting
confidence: 62%
“…23,24,26,27 They also show a lack of TP53 mutations. 6,23,24,28,29 This trend was also recorded in the Asian Cancer Research Group data set. 7 It has been suggested that the profound global DNA effects are responsible for the distinctive clinicopathologic features of EBV gastric cancers 20 including male predominance 9,30 and proximal location.…”
Section: Discussionsupporting
confidence: 62%
“…[35][36][37] The difference in CpG island hypermethylation between intestinal and diffuse types has not been well characterized. Using different DNA methylation markers and different methodology, CpG island methylator phenotype was found to be associated with 'diffuse' histology in some reports 33,38 but not in others. 39,40 These controversial findings are most likely due to the use of differing DNA methylation marker panels as well as methods of analysis.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 99%
“…[21][22][23]30,32,33 However, these previous studies used a small number of CpG island loci by MSP. In our study analyzing 27 CpG island loci by MethyLight, which overcomes some variability problems of MSP, the average MI of EBV-positive GCs and MSI-positive GCs was 0.98 and 0.48, respectively, whereas that of GCs negative for both was 0.37.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 99%
“…The studies of Park et al2 and Shigeyasu et al3 were classified as the multiple gene panel group because over 15 CIMP marker genes were used in each of them. An et al , 4 Ben Ayed‐Guerfali et al , 5 He et al , 6 Ksiaa et al7, and Kusano et al8 were classified as the p16 or MINT ‐based gene panel group, whereas the remaining 3 studies (Chang et al , 9 Chen et al10 and Liu et al11) were classified as the mixed gene panel group because there were no similarities among them. By subgroup analysis, we found that CIMP‐H was significantly associated with poor prognosis in the p16 or MINT ‐based gene panel group, but not in the other 2 subgroups (Figure 1A).…”
Section: Figurementioning
confidence: 99%